2006
DOI: 10.1016/j.vaccine.2006.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying influenza vaccine efficacy and antigenic distance

Abstract: We introduce a new measure of antigenic distance between influenza A vaccine and circulating strains. The measure correlates well with efficacies of the H3N2 influenza A component of the annual vaccine between 1971 and 2004, as do results of a theory of the immune response to influenza following vaccination. This new measure of antigenic distance is correlated with vaccine efficacy to a greater degree than are current state-of-the-art phylogenetic sequence analyzes or ferret antisera inhibition assays. We sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
298
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 142 publications
(305 citation statements)
references
References 44 publications
7
298
0
Order By: Relevance
“…We demonstrated that the informatics framework PREDAC we developed can effectively infer antigenic clusters from HA sequences, and thus can provide a very important tool in the influenza surveillance and vaccine strain recommendation when coupled with large-scale HA sequencing. Previously, many computational approaches were designed to either predict antigenic variants 18,[30][31][32][33][34][35][36] or to model evolutionary patterns for the H3N2 virus [19][20][21]23,24 . In our study, the prediction of antigenic variants and the modeling of antigenic evolutionary patterns are integrated into one computational framework, PREDAC.…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrated that the informatics framework PREDAC we developed can effectively infer antigenic clusters from HA sequences, and thus can provide a very important tool in the influenza surveillance and vaccine strain recommendation when coupled with large-scale HA sequencing. Previously, many computational approaches were designed to either predict antigenic variants 18,[30][31][32][33][34][35][36] or to model evolutionary patterns for the H3N2 virus [19][20][21]23,24 . In our study, the prediction of antigenic variants and the modeling of antigenic evolutionary patterns are integrated into one computational framework, PREDAC.…”
Section: Discussionmentioning
confidence: 99%
“…Each antigenic unit difference in distance between strains increases susceptibility by 7% (Fig. 1C) [1,36,39].…”
Section: Modeling Approach and Choice Of Parametersmentioning
confidence: 99%
“…where c = 0.07 is a constant for converting antigenic distance to a risk of infection [1,36,39]. Each infection mutates to a new antigenic phenotype at a rate ” mutations per day.…”
Section: Model Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical symptoms associated with infection include high fever, headaches, cough, sore throat, runny nose and muscle ache that resolve within several days. Other associated complications of influenza infections include viral pneumonia, secondary bacterial pneumonia, airway inflammation [9,10]. Nasopharyngeal samples are used for the isolation of the virus while using serum samples serological diagnosis can be carried out [3][4][5].…”
Section: Introductionmentioning
confidence: 99%